New findings on compositionally distinct maar volcanoes: A case study from Acıgöl (Nevşehir) caldera (Central Anatolia, Turkey) - Uslular, Göksu; Gençalioğlu Kuşcu, Gonca; Bégué, Florence; Ruch, Joël; Lupi, Matteo; Higgins, Oliver; Caricchi, Luca (Frontiers in Earth Science, 2022)
Acıgöl caldera hosts some of the youngest monogenetic activity (≤ 32 ka) in the Central Anatolian Volcanic Province (CAVP). This activity consists of distinct small-volume intrusions of different compositions. In the western part of the caldera, the successive formation of felsic maars (İnallı, Kalecitepe, Acıgöl, and Korudağ) and lava domes, cluster along a ~10 km-long intrusion with an NW-SE trend. This activity contrasts with a mafic intrusion to the east (~1.5 km long), represented by the syn-formation of the mafic İcik maar and a scoria cone, oriented in the N-S direction. Field observations and physical volcanology reveal that scaled depth, water-magma interaction, and geology of the upper crust are the most significant factors for the depositional characteristics of maars. The juvenile contents of felsic maars are significantly higher than their mafic counterpart, and the lack of accretionary lapilli can be linked to the magma and flow dynamics together with the hydrogeological heterogeneity in the diatremes. The transition between eruption types is rather unstable throughout the stratigraphy of felsic maars (from phreatomagmatic to magmatic), while it is synchronous within the mafic İcik maar. A similar scenario can be followed in the field scale, as the lava domes postdate the maars in the western felsic group, while the formation of the mafic group is possibly coeval. The former case is contradictory to the slightly younger age of Acıgöl maar than the lava dome, which is not supported by our findings. Therefore, we suggest that there is a need for more age data obtained directly from the maar juvenile. The geochemistry of the maar juveniles suggests a similar parental basaltic magma source that has been possibly differentiated by varying degrees of fractional crystallization in time beneath the different parts of the caldera. Our integrated study on the small-volume monogenetic intrusions provides an opportunity to elucidate the role of various factors in the formation of bimodal maar activity, with rarely known felsic maars and their more common mafic counterparts. The youngest activity in the Acıgöl caldera, together with low-velocity anomalies, shallow Curie depths, and prevalent geothermal activity, also warrants further volcanic risk assessment studies.